MEMAHAMI PENTINGNYA PENGALAMAN BELAJAR DI PAUD DESA TELOKO KEC. KAYU AGUNG KABUPATEN OKI DENGAN METODE ANGKA DAN BERHITUNG MENGGUNAKAN SEMPOA - Desvi Wahyuni; Devi Sopiah; Mayang Putri Ariyani; Annisatul Affifah; Muslimah Muslimah; Annisa Kurniawati (Pusat Studi Ekonomi Publikasi Ilmiah dan Pengembangan SDM Azramedia indonesia, 2024)
The introduction of learning to recognize numbers and counting in early childhood has a veryimportant role in early childhood education because it can form children’s basic abilities in matematics. This article discusses the importance of knowing numbers and counting using an abacus through the role of teacher as educators in the Uin Raden Fatah Palembang real Work Lecture Student program with Teloko Village Kec. Kayu Agung, Ogan Komering Ilir Regency, South Sumatera Province. Through a fun approach, children can gain a good undestanding of how to count easily using an abacus, understanding basic mathematical concepts, such as recognizing numbers, and encouraging children to count can help them develop cognitive, social and emotional skills, build children’s confidence in creativity and ability to solve problems. Therefore, the real Work Lecture Program which focuses on thia approach can provide benefits for children’s knowladge.